2012
DOI: 10.1038/bmt.2012.171
|View full text |Cite
|
Sign up to set email alerts
|

Peri-engraftment syndrome in allogeneic hematopoietic SCT

Abstract: Engraftment syndrome (ES) and pre-engraftment syndrome (pre-ES) are both inflammatory conditions that occur after hematopoietic SCT (HSCT) and are characterized by non-infectious fever and skin rash. Although the pathogenesis is not fully understood, both syndromes are similar, and could be defined as a new clinical syndrome, named as peri-engraftment syndrome (peri-ES). We retrospectively analyzed the clinical records in 176 pediatric patients, following allogeneic HSCT. We utilized the definition of ES by Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 20 publications
(34 reference statements)
2
53
2
2
Order By: Relevance
“…Although the pathogenesis is not fully understood, both syndromes are similar, and could be defined as a new clinical syndrome, named as peri-ES. 13 Although this complication has been previously reported in a pediatric transplantation setting, there are no reported data regarding ES in haploidentical pediatric transplantation. The reported incidence of ES in children ranges from 19% to 48% and has been considered a risk factor for developing aGvHD and cGvHD.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although the pathogenesis is not fully understood, both syndromes are similar, and could be defined as a new clinical syndrome, named as peri-ES. 13 Although this complication has been previously reported in a pediatric transplantation setting, there are no reported data regarding ES in haploidentical pediatric transplantation. The reported incidence of ES in children ranges from 19% to 48% and has been considered a risk factor for developing aGvHD and cGvHD.…”
Section: Discussionmentioning
confidence: 80%
“…We were not able to identify risk factors for engraftment failure because of the low number of patients. The median time to neutrophil recovery for the patients with engraftment was 13 days (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The median time to platelet engraftment was 10 days (8-70), and the median times to platelet counts of 50 × 10 9 /L and 100 × 10 9 /L were 13 days (9-150) and 15 days (9-150), respectively.…”
Section: Engraftment Kinetics and Supportive Carementioning
confidence: 98%
“…13,30,31 Schmid et al 13 reported a 48% incidence of ES. Amphotericin treatment and more mononuclear cells in the graft were associated with an increased risk of ES in multivariate analysis.…”
Section: Engraftment Syndromementioning
confidence: 99%
“…Risk factors for ES included age o8 years and transplants from an HLA-mismatched donor. Hong et al 31 used the Spitzer criteria to characterize a periengraftment syndrome after allotransplants. A cumulative ES incidence of 17% was reported with the highest incidence among recipients of double-unit umbilical cord blood transplants, in whom use of total body radiation in the conditioning regimen and early complete chimerism were also risk factors.…”
Section: Engraftment Syndromementioning
confidence: 99%
“…However, it has remained poorly characterized with unclear prognosis or appropriate therapy [20,35]. Several recent studies on PES have come to the following conclusions: (1) common occurrence after UCBT, (2) development before neutrophil recovery, (3) associations with: cyclosporine in GVHD prophylaxis and total body irradiation in conditioning therapy, (4) enhancement of engraftment without significant morbidity as well as early achievement of complete donor chimerism, and (5) controversial association with development of acute GVHD [20,[36][37][38]. -Skin rash -Pulmonary infiltrates -Diarrhea commencing 24 hours before or at any time after the first appearance of neutrophils (1) GVHD prophylaxis using methotrexate in UCBT, (2) use of cyclophosphamide and prednisolone in induction followed by cyclophosphamide mobilization in patients with POEM syndrome, (3) use of donor lymphocyte infusions in relapsed CML after allogeneic HSCT, and (4) steroid prophylaxis significantly decreases the risk of ES following autologous HSCT and is associated with shortened hospitalization without increasing the risk of infection [42][43][44][45].…”
Section: Differential Diagnosismentioning
confidence: 99%